Insultos e ameaças em interações infantis - Maria Auxiliadora Bezerra (Trabalhos em Linguística Aplicada, 2012)
This paper describes insults and threats in children's interactions between children from 6 to 12 years of age in situations involving games, misunderstandings, and the completion of school tasks. The analysis shows that conflict constantly arises in interaction, although explicit vocalization is gradually eliminated as the child acquires strategies of politeness.